Investment climate constraints, network isomorphism and survival among small commercial poultry farms in Ghana. (20th September 2019) - Acheampong, George
The study seeks to the role SME network isomorphism to survival using data from a two-year network survey of poultry enterprises in Ghana. The data was collected between January 2014 and March 2015. The study seeks to understand the usefulness of network isomorphism as structural conformance in a network in aiding the survival of SMEs. Isomorphism was measured as structural equivalence between actors in the collaborative network we developed from the data. First, it is found that there is a high failure rate among the SMEs of about 40%. Secondly, isomorphic SMEs have a better survival probability and such isomorphism was very useful in overcoming investment climate constraints. However, the isomorphism reaches an optimum and returns negative effects. The findings imply that while technical efficiency is important to the survival of enterprises, business managers must also be attuned to the influencing role of structural conformance in an industry.